Metamorphosis of social organisms in light of transformation of cultural boundaries: global consequences of modernization processes - M. V. Silantjeva (Vestnik MGIMO-Universiteta)
The article reveals the fundamental contradictions of the globalization processes that have growing influence on the content and form of intercultural communication in the modern world. The possibilities and prospects of historically new forms of cultural interaction and confrontation.